2010
DOI: 10.1021/jp108659a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pt Doping on the Structure and Visible Light Photoactivity of Titania Nanotubes

Abstract: Platinum-doped titania nanotubes were prepared by a hydrothermal technique to produce visible light activated catalysts. Pt loading, however, also affected the morphology of the titania nanotubes. Scanning electron microscopy and scanning transmission electron microscopy (STEM) results reveal that up to 1 mol % loading Pt-doped titania retains its nanotubular structure, but at 2 and 4 mol % Pt the nanotubes collapse to a nanopowder. High-angle annular dark field STEM images show that the Pt nanoparticles have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 66 publications
7
73
0
1
Order By: Relevance
“…The energy gap decline from 2.840 eV for pure WO 3 film to 2.507 eV for WO 3 /Pt film with the weight percentage of Pt is 4%. Vijayan et al, [8] reported the same result that additional of Pt in the TiO2 nanotube change the optical band gap value. These two findings explain that the addition of Platinum will provide the new energy state slightly below the WO3 conduction band.…”
Section: Resultsmentioning
confidence: 67%
“…The energy gap decline from 2.840 eV for pure WO 3 film to 2.507 eV for WO 3 /Pt film with the weight percentage of Pt is 4%. Vijayan et al, [8] reported the same result that additional of Pt in the TiO2 nanotube change the optical band gap value. These two findings explain that the addition of Platinum will provide the new energy state slightly below the WO3 conduction band.…”
Section: Resultsmentioning
confidence: 67%
“…Hydrothermally grown TiO 2 nanotubes can be doped with various elements including chromium, manganese, cobalt, niobium, vanadium, bismuth, boron, phosphor, gadolinium, platinum, iron, and neodymium 457,458,[460][461][462][464][465][466] . Different co-doped 459,463 and tri-doped 467 TiO 2 nanotubes were also reported.…”
Section: Doping Of Hydrothermal Tubesmentioning
confidence: 99%
“…462,464,465 Liu et al 463 co-doped TiO 2 nanotubes with gadolinium and nitrogen, with 1.5 at.% and 2.3…”
Section: Doping Of Hydrothermal Tubesmentioning
confidence: 99%
“…Furthermore, although a recent review on TiO 2 modified with noble metals recognizes the importance of EPR as a unique tool to understand the superior photocatalytic activity of these materials [9], only few EPR studies have been reported on the topic [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%